1989
DOI: 10.1002/j.1460-2075.1989.tb08565.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of four conserved motifs among the RNA-dependent polymerase encoding elements.

Abstract: Four consensus sequences are conserved with the same linear arrangement in RNA‐dependent DNA polymerases encoded by retroid elements and in RNA‐dependent RNA polymerases encoded by plus‐, minus‐ and double‐strand RNA viruses. One of these motifs corresponds to the YGDD span previously described by Kamer and Argos (1984). These consensus sequences altogether lead to 4 strictly and 18 conservatively maintained amino acids embedded in a large domain of 120 to 210 amino acids. As judged from secondary structure pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
872
2
6

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,110 publications
(910 citation statements)
references
References 101 publications
22
872
2
6
Order By: Relevance
“…Motif A, B, C and D, located in the palm domain, are defined in all classes of polymerases, whereas motif E in the palm domain and motif F in the fingers domain are unique to both RdRps and reverse transcriptases (RTs) (Fig. 1B) (Poch et al, 1989;Hansen et al, 1997;O'Reilly and Kao, 1998). The fingers domain can be further subdivided into five distinct finger motifs, which are named as index, pinky, middle and ring fingers as indicated in the homologous structures in the Picornaviridae family (Ferrer-Orta et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Motif A, B, C and D, located in the palm domain, are defined in all classes of polymerases, whereas motif E in the palm domain and motif F in the fingers domain are unique to both RdRps and reverse transcriptases (RTs) (Fig. 1B) (Poch et al, 1989;Hansen et al, 1997;O'Reilly and Kao, 1998). The fingers domain can be further subdivided into five distinct finger motifs, which are named as index, pinky, middle and ring fingers as indicated in the homologous structures in the Picornaviridae family (Ferrer-Orta et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…[45][46][47] Recent data indicates that the endonuclease activity for pre-mRNA scission and generation of the capped oligomer resides with PA. 48,49 PB1 has intrinsic polymerase activity and is responsible for both mRNA elongation and correct association with the viral RNA template. 50 In contrast to influenza virus, bunya-and arenavirus replication is exclusively cytoplasmic and caps are thus derived from mRNA rather than pre-mRNA. [51][52][53][54][55][56] Since cellular mRNA degradation also occurs in the cytoplasm this raises the question of the relationship between mRNA decay and the bunya-and arenavirus cap-snatching process.…”
Section: Association Of N With the Mrna Degradation Apparatus During mentioning
confidence: 99%
“…Alignment of the five conserved motifs (A to E, indicated by black bars above the alignment) within the polymerase domain was as described by Poch et al [29]. The nearly invariant amino acid residues found in all RNA-dependent polymerases are underlined.…”
Section: Figure 6 Sequence Alignment Of Ty1 and Hiv-1 Rtsmentioning
confidence: 99%
“…The crystal structure of the p66 subunit of HIV-1 RT has shown that the polymerase domain is separated from the RH domain by a connection subdomain which forms a groove between the two active sites and plays a role in binding of the primer-template [22]. Sequence comparison of Ty1 and HIV-1 RTs [29][30][31] shows that the connection domain of the Ty1 enzyme is shorter than the connection domain of the HIV-1 RT (Figure 6). This difference could explain the difference of length of primer-template which can be accommodated between the active sites of the two enzymes.…”
Section: Figure 6 Sequence Alignment Of Ty1 and Hiv-1 Rtsmentioning
confidence: 99%